Research of cosmic rays' variations in july-august 2016 with use of data of the carpet detector (International Journal of Mathematics and Physics, 2016)
The paper reviews the CARPET cosmic ray detector placed into operation at physics and technical faculty of Eurasian National University in 2016. Observation data of the detector provide opportunity of researching nature of cosmic rays induced by processes on the Sun within interplanetary medium and earth's magnetosphere for different time intervals. It also considers results of analysis of cosmic rays' variations and solar flare activity in the period of July-August 2016 taken on the basis of the detector's experimental data, information of neutron monitor network and parameters of solar and geomagnetic activity. The dynamics of experimental data is considered.   GMT АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский        Звуковая функция ограничена 200 символами  Настройки : История : Обратная связь : DonateЗакрыть